The effect and strategy of culinary tourism attraction on tourist visit interest in the City of Solo - Julita Julita; Lice Sari; Holly Felisa (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
The purpose of this study is to identify the potential for culinary tourism in Solo and then find out how much influence it has on the interest of tourist visiting Solo, and from these result it is intended to formulate a strategy for developing culinary tourism in City of Solo which can attract tourist visits to make return visits to City of Solo. This research is a combination of quantitative and qualitative research. Quantitative data analysis was performed by hypothesis testing and coefficient determination to confirm effects expressed as percentage. Meanwhile, qualitative data analysis was continuously conducted in the field and interactively to support, and enrich the data derived from quantitative data. As for the culinary spots themselves, City of Solo has several potential spots in traditional markets, as well as those supported by the government. Based on the analysis, the research shows the impact of culinary tourism on the interest of tourists visiting the city of Solo. The effect of tourist attraction on the interest of tourists visiting the city of Solo is 65.5% and is a significant and positive influence. Then the strategy carried out by the Solo City government for the development of culinary tourism, among others, is to maintain a clean, healthy, neat, and beautiful city. In this case, it can be seen that culinary tourism in a destination such as Solo City can be used as an attraction for tourists so that it can affect the increase in tourist visits.